2019
DOI: 10.1007/s12560-019-09378-0
|View full text |Cite
|
Sign up to set email alerts
|

Glass Wool Concentration Optimization for the Detection of Enveloped and Non-enveloped Waterborne Viruses

Abstract: An extremely affordable virus concentration method based on adsorption-elution to glass wool and subsequent reconcentration through polyethylene glycol 6000 (PEG) precipitation was optimized to recover not only non-enveloped viruses but also enveloped viruses. Hepatitis A virus (HAV) and transmissible gastroenteritis virus (TGEV) were employed as surrogates for naked and enveloped viruses, respectively, to set up the methodology. Initial experimentation in small-volume samples showed that both types of particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 35 publications
0
61
0
Order By: Relevance
“…Results also showed that GW filtration resulted in higher recoveries of the non-enveloped virus Poliovirus 3 (57.9%) compared to the other non-enveloped viruses (Bovine Coronavirus = 18.1%, Bovine Rotavirus group A = 22.1%, Bovine Viral Diarrhea Virus [type 1 and 2] = 15.6-19.7%) [ 77 ]. Blanco et al [ 78 ] employed adsorption/elution onto GW and PEG precipitation for the concentration of the porcine coronavirus Transmissible Gastroenteritis Virus (TGEV) and the non-enveloped Hepatitis A virus (HAV) in environmental samples. The results have shown that the recovery of TGEV was improved by increasing the GW and eluent contact time and the elution pH, increasing PEG concentration, or performing the elution either by recirculation or under agitation.…”
Section: Main Considerations Related To the Development Of A Methodolmentioning
confidence: 99%
“…Results also showed that GW filtration resulted in higher recoveries of the non-enveloped virus Poliovirus 3 (57.9%) compared to the other non-enveloped viruses (Bovine Coronavirus = 18.1%, Bovine Rotavirus group A = 22.1%, Bovine Viral Diarrhea Virus [type 1 and 2] = 15.6-19.7%) [ 77 ]. Blanco et al [ 78 ] employed adsorption/elution onto GW and PEG precipitation for the concentration of the porcine coronavirus Transmissible Gastroenteritis Virus (TGEV) and the non-enveloped Hepatitis A virus (HAV) in environmental samples. The results have shown that the recovery of TGEV was improved by increasing the GW and eluent contact time and the elution pH, increasing PEG concentration, or performing the elution either by recirculation or under agitation.…”
Section: Main Considerations Related To the Development Of A Methodolmentioning
confidence: 99%
“…These should be considered in the case of VIRADEL recovery of CoVs where virus elution from electronegative or electropositive membranes is performed at strong alkaline or acid pH, respectively. Five studies have examined the efficiency of recovery of CoVs: the recovery of bovine enteric CoV ( Collomb et al, 1986 ), SARS-CoV-1 ( Wang et al, 2005a ), murine hepatitis virus (MHV)( Ye et al, 2016b ), bovine CoV( Abd-Elmaksoud et al, 2014 ), and transmissible gastroenteritis virus (TGEV) ( Blanco et al, 2019 ). Adsorption on glass wool and glass powder ( Abd-Elmaksoud et al, 2014 ; Blanco et al, 2019 ; Collomb et al, 1986 ) or on silica gel compounded with aluminum hydroxide ( Wang et al, 2005a ), followed by elution with neutral ( Wang et al, 2005a ) or alkaline ( Abd-Elmaksoud et al, 2014 ; Blanco et al, 2019 ; Collomb et al, 1986 ) buffers were some of the techniques adopted for the concentration of the above mentioned CoVs.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Ultrafiltration was demonstrated the most efficient method with 25.1% of recovery of MHV. Blanco et al (2019) applying virus adsorption onto glass wool with subsequent elution with alkaline buffer and PEG precipitation, explored on the recovery of TGEV, effects of pH, contact time and composition of eluent. An adsorption of 42.7% and the complete removal of virus from the glass wool adsorbent was obtained by overnight elution with glycine/beef extract buffer at pH of 11.0 in presence of TWEEN 80 (0.3%).…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Earlier studies [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] showed the occurrence of CoV in wastewater samples ( Table 2 ). Wastewater originating from the hospital during the SARS-CoV-1 outbreak was tested for its virulence/occurrence before and after disinfection using a symptomatic patient sample as a benchmark [51] .…”
Section: Occurrence Of Virus In Environmental Matrixmentioning
confidence: 84%
“…Surface water (river, lake, and water reservoir) detected 37 families with a genetic material (dsDNA, ssDNA, and ssRNA) of which dsDNA samples were mostly related to bacteriophages and the majority of sequences related to families of Coronaviridae, Reoviridae and Herpesviridae [54] . Another study on the detection of CoV from surface water using hepatitis A virus (HAV) as a benchmark using semi-nested, real-time reverse transcriptase-polymerase chain reaction (RT-PCR) and quantitative RT-PCR (qRT-PCR) found positive for CoV to the lineage A of alpha-coronavirus (αCoV) related to the rodent clade [55] . Water treatment plants are also susceptible to have viral contamination and pose the possibility to transmit through water distribution if not fully inactivated [45] .…”
Section: Occurrence Of Virus In Environmental Matrixmentioning
confidence: 99%